Improving Community Social Relationships through Education and Competition Activities in Timbang Lawan Village - Imsar ,M.S; Rifaldi Dwi Syahputra; Syakira Rifdhayani Yoes; Putri Khairani Pratiwi; Ogi Rahmadana (Edumaspul: Jurnal Pendidikan, 2023)
The research that has been conducted is entitled "Improving Community Social Relations through Competition Activities in Timbang Lawan Village". The purpose of this study is This study aims to determine the concept of community social relations in Timbang Lawan Village and the concept of competition activities in Islam, as well as competitions held in Timbang Lawan Village so as to improve community social relations. This study used descriptive qualitative methods with data collection techniques using observation, interviews and documentation. Researchers use data analysis techniques that suggest an activity in analyzing qualitative data that is carried out interactively and continues continuously to completion. After the data was analyzed, the results of the study showed The results of this study showed that with the implementation of the MTQ competition and celebrating Indonesia's independence day on August 17, the social relations of Timbang Lawan villagers were getting closer, because without realizing it, the competitions were seen only as entertainment, but behind that there was a lot of education that stimulated residents in improving higher social relations.